Urbanity and urbanization: an interdisciplinary review combining cultural and physical approaches. - Schneider, Christoph; Achilles, Bianca; Merbitz, Hendrik (MDPI, 2014)
This review paper focuses on research schemes regarding urbanity and urbanization, and brings together both cultural and physical approaches. First, we review the cultural and social construction of urbanity (as related to urbanization) in Germany. In the early 20th century, urbanity was mainly the result of identity derived from a historical perspective in cities. This has changed profoundly in recent decades as urbanity stems more and more from various urban lifestyles and the staging of societal experiences, as summarized in the German term, "Erlebnisgesellschaft" (thrill-seeking society). The discussion is extended by an assessment of the recent state of the art regarding physical urban research. The focus lies on different fields of research; we address topics such as biodiversity, urban climate, air pollution, and resilience, as well as their impact on urban planning and governance. In conclusion, in order to tackle recent developments and future challenges regarding social and environmental issues, an integrative approach urges novel cross- and inter-disciplinary research efforts in urban studies, including urban-rural linkages. A newly constituted assessment of urbanization and city quarter development is proposed; the assessment focuses on the conjoint analysis of mobility, "Energiewende" (energy transition), cultural drivers, demographic development, and environmental issues.
Keywords: Stadtplanung; Urbanität; Stadtentwicklung; Stadtklima; Stadtökologie; Mobilität; Urbanisierung; Klimawandel; Energiewende; Stadtgesellschaft; Diversität; Nachhaltige Stadtentwicklung